2013
DOI: 10.1590/s1516-31802013000100006
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E for prevention of oxaliplatin-induced peripheral neuropathy: a pilot randomized clinical trial

Abstract: CONTEXT AND OBJECTIVE: Oxaliplatin is one of the chemotherapy regimens most used for treating colorectal cancer. One of the main limitations to its use is induction of peripheral neuropathy. Previous studies have shown that vitamin E can reduce the incidence of peripheral neuropathy by 50%. This study aimed to assess the effectiveness of vitamin E for prevention of oxaliplatin-induced peripheral neuropathy. DESIGN AND SETTING: Prospective, phase II, randomized pilot study developed at a university hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 11 publications
0
38
0
1
Order By: Relevance
“…In fact, daily infusions of an investigational prophylactic CIPN treatment throughout the full course of chemotherapy are not likely to be feasible. On the contrary, oral or topical medications that target the nervous system – such as anti-epileptics, anti-depressants, or anti-inflammatory agents that are being used to decrease pain or augment pain inhibition – would likely best be initiated before the start of chemotherapy and continued until the end of chemotherapy (e.g., [1,75,92]) or for 2 weeks to 3 months after chemotherapy completion (e.g., [8,9,63,128,129]).…”
Section: Design Considerations In the Context Of 4 Illustrative Prmentioning
confidence: 99%
“…In fact, daily infusions of an investigational prophylactic CIPN treatment throughout the full course of chemotherapy are not likely to be feasible. On the contrary, oral or topical medications that target the nervous system – such as anti-epileptics, anti-depressants, or anti-inflammatory agents that are being used to decrease pain or augment pain inhibition – would likely best be initiated before the start of chemotherapy and continued until the end of chemotherapy (e.g., [1,75,92]) or for 2 weeks to 3 months after chemotherapy completion (e.g., [8,9,63,128,129]).…”
Section: Design Considerations In the Context Of 4 Illustrative Prmentioning
confidence: 99%
“…Numerous studies have examined the role of vitamin E in reducing the risk of CIPN occurrence; however, some aspects of this relation still remain controversial. Pace et al Afonseca et al have reported no significant effect for vitamin E on the occurrence of oxaliplatin-induced neuropathy (8). Thus, more research should be conducted to explain how vitamin E could act as a neuroprotective agent in this context.…”
Section: Introductionmentioning
confidence: 98%
“…The bulk of evidence is negative for both scenarios [12], [14], [19], [20], with rare exceptions [17], [21]. Importantly, the large majority of studies have not used validated pain measurement tools [10], [11], [13], [14], [16], [19], [22], [23], while most have used the common terminology criteria (CTC) adverse events grading system as the primary outcome measurement. While this choice is sound and supported by robust evidence [24], it must be kept in mind that most patients with OXAIPN have small‐fiber‐predominant polyneuropathy [1], which has as its main symptom neuropathic pain.…”
mentioning
confidence: 99%